Hydrodynamic variability in the Southern Bight of the North Sea in response to typical atmospheric and tidal regimes. Benefit of using a high resolution model. (October 2020) - Ivanov, Evgeny; Capet, Arthur; Barth, Alexander; Delhez, Eric J.M.; Soetaert, Karline; Grégoire, Marilaure
Abstract: In this paper, the hydrodynamics of the Southern Bight of the North Sea (SBNS) and in particular, the Belgian Coastal Zone (BCZ) is investigated on daily to seasonal time scales using a high resolution hydrodynamical model. The Regional Ocean Modeling System (ROMS) is implemented over the SBNS with 5 km resolution and downscaled at 1 km resolution over the BCZ in a two-way nesting configuration run over a three years period (i.e. 2006–2008). The benefit of using a high resolution model over the BCZ is assessed through an extensive comparison of model results with data from satellite and in-situ fixed platforms as well as reference products available for the region. The validation exercise and the results analysis are conducted with a particular focus on hydrodynamic features that are expected to impact the sediment transport. We find that despite the validation procedure does not allow to clearly demonstrate better performance of the high resolution model compared to the coarse resolution model in terms of overtidal circulation, sea surface temperature (SST) and salinity (SSS), the high resolution model resolves additional details in the variability of residual circulation and Scheldt salinity plume dynamics. The analysis of the response of the simulated hydrodynamics to atmospheric regimes for neap and spring tide highlights the major role played by the wind direction on the averaged currents and plume extension. The strongest currents and minimum plume extension are obtained under southwestern winds and neap tide while when northeastern winds prevail, the plume extension is at its maximum and the circulation is the weakest. We show that while neap tides allow the establishment of streamlined circulation, the spring tides induce more turbulent circulation which can favor the retention of transported elements. This latter property could not be resolved with the 5 km resolution model. Highlights: Two-way nested ROMS models (1 and 5 km) are set for the Belgian Coastal Zone. Benefits of high resolution in resolving variability of local dynamics are assessed. Only 1 km reveals distinct mesoscale activity during spring and neap tides. Dominant wind regimes reverse the regional circulation and affect plume extension. Model skill metrics are not systematically enhanced by high resolution.